Battery energy-storage system: A review of technologies, optimization objectives, constraints, approaches, and outstanding issues - Hannan M.A.; Wali S.B.; Ker P.J.; Rahman M.S.A.; Mansor M.; Ramachandaramurthy V.K.; Muttaqi K.M.; Mahlia T.M.I.; Dong Z.Y. (Elsevier Ltd, 2023)
Electric batteries; Fossil fuels; Global warming; Photovoltaic cells; Population statistics; Wind power; Battery energy storage systems; Carbon emissions; Constraint; Fossil fuel burning; Objective functions; Optimization algorithms; Rapid growth; Review of technologies; Sizing; Technology optimization; Optimization